Identification of novel Arf1 GTPase inhibitors for cancer target validation - Mqwathi, Nomxolisi Vuyokasi (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology)
The key regulators of both anterograde and retrograde vesicular traffic, adenosine diphosphate-ribosylation factors (Arfs), also coordinate various signalling pathways and regulate cellular processes required for cell survival and function. In addition to its role in mediating secretory trafficking in the Golgi apparatus, the involvement of Arf1 in signalling pathways that contribute to the formation and progression of cancer has become apparent, and the overexpression and deregulation of Arf1 activity has been associated with cancer cell invasion, proliferation and metastasis. As with other small GTPases, Arf1 must cycle back and forth between an inactive (GDP-bound) and active (GTP-bound) conformation to carry out its function. However, the cycle of Arf1 inactivation and activation is controlled by Arf GTPase activating proteins (Arf-GAPs) that stimulate Arf1 to hydrolyse the bound GTP to GDP and Arf guanine nucleotide exchange factors (Arf-GEFs) that facilitate GDP for GTP exchange on Arf1, respectively. The identification of Arf1 inhibitors that indirectly disrupt Arf1 function by blocking its interaction with Arf-GAPs or Arf-GEFs has generated interest in their use as possible anti-cancer agents. The suppression of Arf1 activation (by targeting Arf-GEFs) has been investigated as a potential cancer therapeutic target and resulted in inhibitor compounds that have micromolar-range activity against cancer cells and targets and promising results in mouse models, but experience problems with bioavailability when used in vivo. This motivates the search for novel Arf1 inhibitors for validation purposes to question whether Arf1 is a viable target for cancer therapy. The purpose of the study was to employ a recently developed colourimetric screening assay to identify inhibitors of Arf1 activation (Arf-GEF inhibitors) and deactivation (Arf-GAP inhibitors), with a focus on evaluating the potential of Arf1 deactivation as an entirely novel anti-cancer target. The proteins required for the assay (Arf1, Arf-GEF and -GAP domains and a reporter protein, GST-GGA3) were expressed in E. coli. and purified using affinity chromatography. The assay could detect the activation of Arf1 by the catalytic Sec7 domain of the three Arf-GEFs chosen for this study, but reproducibility was compromised by the occasional spontaneous activation of Arf1 in the absence of the Arf-GEFs. By contrast, the assay could reproducibly detect Arf1 deactivation by an Arf-GAP domain (Arf-GAP1GAP) and was subsequently used to screen a library of Î±-helix mimetics. Thirteen hit compounds with IC50 values ranging from 0.53 to 20.95 Î¼M were found to inhibit Arf-GAP1GAP-mediated stimulation of GTP hydrolysis by Arf1-GTP in this assay format, however, they did not effectively suppress the proliferation of three tested cell lines (HeLa, MCF-7 and MCF-12A). Interestingly, the results obtained from fluorescence microscopy studies suggested that the compounds disrupt Golgi structure and Arf1 localisation, presumably by keeping Arf1 in its active conformation by blocking Arf-GAP1 function. This suggests that the compounds affect Arf1 function in cells, and may be used to explore the feasibility of targeting Arf1 deactivation for anti-cancer purposes in a wider range of cell lines and experiments. It has been reported that Arf-GAP1 inhibition is associated with the suppression of cell migration, and the potential of the compounds as metastasis inhibitors may also be explored.
Keywords: ARF1; GTPase; Guanosine triphosphatase; Cancer -- Treatment